Improving Comprehension of Numbers in the News - Barrio, Pablo J.; Goldstein, Daniel G.; Hofman, Jake (Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
How many guns are there in the United States? What is the incidence of breast cancer? Is a billion dollar budget cut large or small? Advocates of scientific and civic literacy are concerned with improving how people estimate and comprehend risks, measurements, and frequencies, but relatively little progress has been made in this direction. In this article we describe and test a framework to help people comprehend numerical measurements in everyday settings through simple sentences, termed perspectives, that employ ratios, ranks, and unit changes to make them easier to understand. We use a crowdsourced system to generate perspectives for a wide range of numbers taken from online news articles. We then test the effectiveness of these perspectives in three randomized, online experiments involving over 3,200 participants. We find that perspective clauses substantially improve people’s ability to recall measurements they have read, estimate ones they have not, and detect errors in manipulated measurements. We see this as the first of many steps in leveraging digital platforms to improve numeracy among online readers.